VULNERABILITY OF ELDERLY IN THEIR HOME ENVIRONMENT AT HIGH DENSELY SETTLEMENT - Pramitasari, Diananta; Sarwadi, Ahmad (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2019)
Abstract_ This study basically aims to examine the vulnerability of the elderly when they are using the space in their home within a high densely settlement. Due to the high density of the urban settlement, the condition of the elderly living unit that located in the middle of settlement area is questioned. Under the condition of lack of space, actually two questions are appeared. First question is “how do the elderly residents use the space for their daily life?”. Moreover, the second question is about “is the room as well the home environment good enough for supporting the elderly daily activities and maintaining their health?” These questions are actually directing to necessary of examining the vulnerability the elderly in their own home. This study was carried out through conducting field observation and doing the individual interview in two neighborhoods located at the city center of Yogyakarta City. By interviewing the elderly residents this study identified the room or spaces that most frequently used the senior residents during their lives inside their own home. The identification then proceeds in to the assessment of the space condition especially related to the natural lighting and ventilation. This study found that in urban settlement with high density and aging population, there was subtle vulnerability existed in the spaces within the elderly’s home that most frequently used. This vulnerability was sourced at the conditions of natural lighting and fresh air ventilation that performed by the home environment properties. These physical aspects of the space considered significant since the resident houses were in very limited urban spaces. Although the vulnerability is subtle or slight, this condition indicates that the elderly residents’ health is really threatened.Keywords: Elderly; Home Environment; High Densely Settlement; Use of Space; Vulnerability.